The association of CAG repeat length polymorphisms of androgen receptor gene and spermatogenesis impairment in several Indonesian men (Faculty of Medicine Universitas Indonesia, 2004)
Spermatogenesis impairment is the main cause of infertility in men. Androgen is believed to play a critical role in regulating spermatogenesis. Androgen acts by binding to the androgen receptor (AR) which is a protein regulator of DNA transcription. Exon 1 of AR gene contains a CAG repeat length polymorphism and it is believed to interfere AR function. This study includes DNA isolation from peripheral blood and amplification of CAG repeat fragments by PCR method. CAG repeat lengths were determined by electrophoresis on 6% denaturing gel polyacrylamide. We found that the mean CAG repeat lengths were 24,3 ± 3,4 in oligozoospermic/azoospermic men and 22,7 ± 2,7 in normozoospermic men. The difference in CAG repeat length between the two groups was statistically significant (p = 0,031, t-test). Nevertheless, there was no correlation between CAG repeat lengths and sperms concentration (rs = -0,038; p = 0,775). This result suggest that the expansion of CAG repeat length was not the main cause of spermatogenesis impairment. (Med J Indones 2004; 13: 215-20)